(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Crime has a massive impact on society. When people are wronged in any way—whether physically, socially, or monetarily—they have a right to seek redress. There has been growing consensus in latest generations that victims of crime should really be addressed with respect and their fundamental rights must be safeguarded, and that criminal cases competence should shift to reflect this reality. A new subfield of crime, victimology, has emerged in recent years to better comprehend victims’ experiences. As the situation of crime victims is not improving anywhere in the globe, recompense for them is a major cause for worry. The purpose of compensation is straightforward: it vindicates the victim’s claim to financial restitution for wrongs committed against them or their property. Several sections of the Code of Criminal Procedure, the Probation of Abusers Act of 1958, and the Motor Vehicle Act of 1988 all make reference to this. This study examines victim remuneration from several angles, including the victims’ point of view, the need of grievance redressal, Indian regulations and legislation, and the current judicial trend.